2015
DOI: 10.1007/s11368-015-1295-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in soil macropores measured using tension infiltrometer under different land uses and slope positions in subtropical China

Abstract: Purpose Soil macropores play a principal role in water infiltration but they are highly variable. The objectives of this study were (1) to investigate the temporal change in macropores of an Ultisol as affected by land use and slope position and (2) to analyze contribution of macropores to water infiltration. Materials and methods Water infiltration was measured at upper and lower slopes in citrus orchard and watermelon field once every 2 months for 1 year using tension infiltrometers at a successive pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…In 2013 and 2014, the K h0 was increasing as topsoil was consolidating after tillage, which is in agreement with other studies [57,58]. This trend suggests that the loose soil after tillage has a high proportion of larger inter-aggregate voids that decrease water flux during unsaturated conditions [20].…”
Section: Tension Infiltration Experimentssupporting
confidence: 89%
“…In 2013 and 2014, the K h0 was increasing as topsoil was consolidating after tillage, which is in agreement with other studies [57,58]. This trend suggests that the loose soil after tillage has a high proportion of larger inter-aggregate voids that decrease water flux during unsaturated conditions [20].…”
Section: Tension Infiltration Experimentssupporting
confidence: 89%
“…The number of each pore size class (e.g., > 0.5, 0.25–0.5 mm), N (m −2 ) was determined as follows (Watson & Luxmoore, 1986; Wilson & Luxmoore, 1988): N=8μ[]K()ψiKfalse(ψi1italicρgπr45.2emi=1,2,normaln Where: μ is the viscosity coefficient of water (N m −2 s −1 ), ρ is the water density (kg cm −3 ), and r is the lower limit of equivalent pores radius (cm). Effective pores indicate that the pores conduct water actively (Zhang et al, 2016). Effective porosity (cm 3 m −3 ) of each pore size class (e.g., > 0.5, 0.25–0.5 mm), θ e , was given by (Watson & Luxmoore, 1986; Wilson & Luxmoore, 1988): θe=8μ[]K()ψiKfalse(ψi1ρgr25.2emi=1,2,normaln …”
Section: Methodsmentioning
confidence: 99%
“…Conventional tillage has been found to destroy the connectivity of soil macropores and further alter hydraulic conductivity and porosity (Buczko et al, 2006). The vegetation cover types affect the effective porosity and control the ratio of water that flows through macropores and mesopores (Bodhinayake & Si, 2004; Holden, 2009; Zhang, Lin, Wang, & Peng, 2016). Soil pore structure and macropores are highly correlated with soil hydraulic properties in different habitat types.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, even lower than that under tillage treatment, as in deeply tilled soils, intensive tilled soil pores are formed primarily by the tillage tool. Similarly, Zhang et al (2016) concluded that No-tillage although increased water conducting macropores but did not increase hydraulic conductivity. However, our results are contradictory with soil macroporosity under no-tillage is usually higher (Bodhinayake and Si, 2004;Coquet et al, 2005;Moret and Arrúe, 2007) under tilled soil.…”
Section: Surface Runoffmentioning
confidence: 98%